2006
DOI: 10.1158/1535-7163.mct-06-0115
|View full text |Cite
|
Sign up to set email alerts
|

Development of engineered antibodies specific for the Müllerian inhibiting substance type II receptor: a promising candidate for targeted therapy of ovarian cancer

Abstract: The Müllerian inhibiting substance type II receptor (MISIIR) is involved in Müllerian duct regression as part of the development of the male reproductive system. In adult females, MISIIR is present on ovarian surface epithelium and is frequently expressed on human epithelial ovarian cancer cells. Müllerian inhibiting substance has been found to be capable of inhibiting the growth of primary human ovarian cancer cells derived from ascites and ovarian cancer cell lines. This suggested to us that MISIIR could be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 58 publications
1
15
0
Order By: Relevance
“…The production of purified, fully cleaved AMH has been achieved only recently, 51 and with this AMH one would need only 1:1000 of the dose compared with partially cleaved AMH. Targeting AMHRII with activating antibodies 62 or small molecule agonists 23,59 presents another attractive option for supplementary treatment of AMHRII-positive advanced or recurrent GCTs. Nevertheless, the observed activation of apoptosis in GCTs may not necessarily involve AMHRII, given that the doses used in this study are more robust than implicated by the reported K d for AMH to AMHRII.…”
Section: Discussionmentioning
confidence: 99%
“…The production of purified, fully cleaved AMH has been achieved only recently, 51 and with this AMH one would need only 1:1000 of the dose compared with partially cleaved AMH. Targeting AMHRII with activating antibodies 62 or small molecule agonists 23,59 presents another attractive option for supplementary treatment of AMHRII-positive advanced or recurrent GCTs. Nevertheless, the observed activation of apoptosis in GCTs may not necessarily involve AMHRII, given that the doses used in this study are more robust than implicated by the reported K d for AMH to AMHRII.…”
Section: Discussionmentioning
confidence: 99%
“…The “dead” D3 scFv was isolated from a human phage-display library (Yuan et al, 2006) and binds to an epitope formed by the junction between a biotinylated peptide and streptavidin. Binding, as measured by surface plasmon resonance (SPR) on a BIAcore1000 (BIAcore, Piscataway, NJ), requires the presence of both the peptide and SA; binding cannot be competed with either of the components alone.…”
Section: Methodsmentioning
confidence: 99%
“…Binding of the A5 and the ALM bs-scFv, to ErbB2 and ErbB3 extracellular domains (ECDs) was characterized by SPR using ErbB2 and ErbB3 ECDs (Horak et al, 2005) as target antigens and methods described previously (Yuan et al, 2006). ECDs were diluted to 10 μg/mL in 10mM sodium acetate pH 5.2 and approximately 200 RU of ECDs were immobilized onto CM5 sensor chips via NHS-ester chemistry.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, homodimerization but not heterotetramerization is necessary for correct folding, which could allow for more efficient expression. In general, scFv-Fcs exhibit characteristics equivalent to their parent IgG (Shu et al, 1993;Powers et al, 2001;Cao et al, 2009) and have been tested for similar applications (Li et al, 2000;Yuan et al, 2006;Mori and Kim, 2008;De Lorenzo and D'Alessio, 2009;Olafsen et al, 2009;Riccio et al, 2009). …”
mentioning
confidence: 99%